FAKTOR-FAKTOR YANG MEMPENGARUHI PERUSHAAN DALAM MELAKUKAN AUDITOR SWITCHING (Media Riset Akuntansi, 2022)
This research aims to analyze the factors that influence the company to auditor switching in Indonesia. The metode sampling in this research used is purposive sampling. According to the result of research that had been done on manufacturing company that listed in Indonesia Stock Exchange, we can concludes that previous year’s audit opinion and financial distress didn’t have influences on auditor switching, while audit delay have influences on auditor switching. Auditor opinion variable didn’t have influences is suspected because the company are avoiding the risk of opinion shopping. Financial distress didn’t have any influences is suspected because the cost of start-up from a new auditor is relatively expensive. An influential audit delay is thought to be due to the length of time the completion of the independent audit report.